Please do question no.13
I need step-by-step explanation.
Attachments:
![](https://hi-static.z-dn.net/files/d4c/52f4c5e46c567cbaabe42f523ea9ed65.jpg)
Answers
Answered by
1
Answer:
Hi, this is the answer for ur question
let x be my age
then
According to the question
hope it helps
Attachments:
![](https://hi-static.z-dn.net/files/d67/2726f2b05c57477a92fddaf97e4f08e3.jpg)
Answered by
1
Answer:
Step-by-step explanation
Let the present age be x years
6 years ago the age was x-6 years
Thrice the age 6 years ago = 3(x-6)
Twice the present age = 2x
As per question if thrice the age 6 years ago us subtracted from twice the present age, the result us present age. So the equation becomes
2x - 3(x-6) = x
2x -3x +18 = x
2x -3x -x = -18
-2x = -18
x = -18/-2 = 9 years.
Option D
Pls mark as brainliest
Similar questions